PROSEDUR PENGELUARAN BIAYA PERJALANAN DINAS DI KEMENTERIAN KOPERASI DAN UKM BIDANG USAHA MIKRO - Vara Nisrina Khalilah, (2023)
In making this final project, the aim is to apply the knowledge gained during three years in college and to further develop the knowledge and understanding gained. The results in this study stated that the Ministry of Cooperatives and SMEs is a work unit within the Supreme Audit Agency of the Republic of Indonesia whose main task is to carry out inspections. Concerning the management and responsibility of state finances in the community, accountability for official travel and regulated by the Minister of Finance's Official Travel Regulations KEMENKOP uses the at-cost method for payment, especially in calculating official travel. Notification of official travel responsibilities is carried out no later than 5 (five) days after the end of the official trip, by compiling bookkeeping documents consisting of the 2nd sheet of SPD.